Potensi Tindak Pidana Kriminal oleh Anak Remaja ditinjau dari Faktor Umur dan Pendidikan dengan Metode Multi Factor Evaluation Process (MFEP) - Limbong, Riswan; Siregar, Kristian (LPPM UNIKA Santo Thomas Medan, 2018)
According to statistics in 2013 there were 535 cases and in 2014 there were 723 cases, and based on the data there was an increase of Â± 1.35%. The cause of this crime is caused by many factors, but if the factors that cause this crime are known to be earlier by the parents (community), perhaps parents can educate their children and can reduce the number of juvenile perpetrators of physical criminal offenses. The physical crimes referred to in this study are: Robbery, Public order theft and murder. Multifactor Evaluation Process (MFEP) is a quantitative method that uses a